Managerial Competencies in Knowledge Context: Comparative Analysis of Poland and United Kingdom - Agnieszka Sitko-Lutek; Monika Jakubiak (International School for Social and Business Studies, 2014)
The present study aims at defining the importance of the managerial competencies, taking particular interest in knowledge, in students' prospective professional career and the level in which these competencies were gained in the course of their studies. The empirical material was collected on the basis of a diagnostic survey carried out from 2009 to 2010 in Lublin, Poland and Huddersfield, Great Britain. The group of respondents consisted of the final year university students of economics and management. The research results revealed that, among both respondent groups, the importance of evaluated competencies exceeded the level of competencies gained during their studies.